2017
DOI: 10.1002/jcb.25893
|View full text |Cite
|
Sign up to set email alerts
|

UXT Is a LOX-PP Interacting Protein That Modulates Estrogen Receptor Alpha Activity in Breast Cancer Cells

Abstract: The lysyl oxidase proenzyme propeptide region (LOX-PP) is a tumor suppressor protein whose mechanism of action is not completely understood. Here, the Ubiquitously expressed Transcript (UXT) was identified in a yeast two-hybrid assay with LOX-PP as bait and confirmed as a novel LOX-PP associating protein. UXT, a prefoldin-like protein, is ubiquitous in human and mouse. Since UXT modulates androgen receptor transcriptional activity in prostate cancer, we studied its role in breast cancer. Breast tumors and deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
0
14
0
3
Order By: Relevance
“…Interestingly, interaction between EVI1 and NF-κB has been reported to be important in genomic stability in leukemia [8]. Recent functional studies characterized UXT’s interaction with nuclear receptors, such as ER and AR [9, 10]. Our previous work identified UXT as a transcription factor that directly binds to the AR N-terminus and modulates AR transcriptional activity in prostate cancer cells [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, interaction between EVI1 and NF-κB has been reported to be important in genomic stability in leukemia [8]. Recent functional studies characterized UXT’s interaction with nuclear receptors, such as ER and AR [9, 10]. Our previous work identified UXT as a transcription factor that directly binds to the AR N-terminus and modulates AR transcriptional activity in prostate cancer cells [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, LOX-PP has been found in the nucleus of several cell types 16 , 17 , and colocalizes with the microtubule network in osteoblastic cells 17 . LOX-PP interacts with intracellular or nuclear proteins, namely HSP70 and c-Raf, CIN85, UXT 18 20 and with the intracellular phosphatase domains of receptor-type protein tyrosine phosphatase kappa 21 . The major uptake pathway of recombinant LOX-PP is phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)-dependent micropinocytosis, while a secondary pathway depends on dynamin and caveolae 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we identi ed that UXT is also more abundant in breast cancer tissues or cells than normal tissues or cells through analyzing its expression in specimens from breast cancer patients and breast cancer cells, respectively. The reasons for UXT involving in tumor progress were often attributed to enhancing NF-κB activities through forming an integral component of the NF-κB enhanceosome [20], corrupting centrosome activity by forming a novel component of centrosomal processes associated with γ-tubulin [5],or interacting with estrogen receptor or androgen receptor [21,22], and so on. In the present study, we found that UXT negatively regulates the MEG3/p53 axis in a DNMT3bdependent manner to promote the apoptosis and inhibit migration and invasion of breast cancer cells, as well as the growth of nude mice xenograft.…”
Section: Discussionmentioning
confidence: 99%